The Effect of Student Participation in Organizing HIMA Family Welfare Education on Student Learning Achievement - Asiani Abu (JOLADU: Journal of Language Education, 2023)
This research aims to determine: 1) an overview of the influence of participation in organizations at Hima PKK on student learning achievement; 2) learning achievement before and during organizing at Hima PKK; and 3) the influence of student participation in organizations on student learning achievement at Hima PKK. This research is a quantitative study using the ex post facto method. The sampling technique uses a saturated sampling technique. Data collection techniques using observation, questionnaires, and documentation The data analysis technique uses descriptive statistical analysis and inferential statistical analysis to explain the influence between variables. Based on the research results, it was found that 1) the picture of the influence of student participation in organizations on learning achievement is very well presented with four indicators: level of attendance at meetings, position held, providing suggestions, criticism, and opinions for improving the organization, Willingness of members to make sacrifices and member motivation 2) Learning achievement before and during the organization at Hima PKK is that out of 30 students, there are 20 students with the highest score with a very good predicate with a percentage of 66.6%, while those with the second highest score with a good predicate are 8 people with a percentage of 26.6%. 3) Based on data analysis, it shows that the influence of participation in organizing at Hima PKK on student learning achievement is at a low percentage of 22.9%. This shows that participation in organizations does not have a bad effect on student learning achievement because there are 77.1% other variables that influence it.